Dampak Pariwisata Terhadap Kesejahteraan Masyarakat Desa Sekapuk Kecamatan Ujungpangkah Kabupaten Gresik - Syarifullah, Achmad Dienil Wachidi; Rachmawati, Lucky (Jurnal Ekonomika : INDEPENDEN, 2023)
Tourism is seen as a business with economic value, which is quite promising today. Tourism is a process that can add value to goods or services as a single product, both visible and invisible or intangible. Currently tourism can be made. Sekapuk Village currently has a tourist spot called Setigi Tourism. With this tourist spot, the village and community economy is expected to increase. This study aims to examine and analyze the tourism sector on the welfare of the people in Sekapuk village. This study used a qualitative research method with a descriptive approach. The results of this study indicate that tourism has a role in realizing the welfare of the surrounding community.